Evaluasi Kromatin Sperma Sebagai Indikator Kualitas Sperma - Ahmad Syauqy (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT There are infertility cases that is founded on man, which can’t be explained. It encourages androlog and the researcher to find another examination besides men’s fertility examination as commonly use in clinic. Nowadays, sperm chomatin is not become a clinical parameter in deciding man fertility yet. According to some researchers, abnormality in sperm chromatin can influence infertility in men. Sperm chromatin’s examination that is commonly use is aniline blue and toluidine blue examination. Aniline blue examination is used to see chromatin’s sperm maturity and toluidine blue examination is used to see packaging of sperm chromatin. Some researchers told that aniline blue and toluidine blue examination is recomended to complete semen’s analysis in men’s fertility examination. Keywords: sperm chromatin, quality of sperm